Blood lactate concentrations in elite Polish 100 m sprinters - Kawczynski, A.; Kobialka, K.; Mroczek, D.; Chmura, P.; Maszczyk, A.; Zajac, A.; Chmura. J. (International Journal of Performance Analysis in Sport, 2015)
The main objective of this study was to show and analyse the changes in blood lactate concentrations in Polish elite sprinters. The study sample was comprised of 9 top male sprinters and 8 top female sprinters, all finalists from the Polish national championships. Blood lactate concentrations were evaluated with the use of a Lactate Scout measuring device. The measurements were taken pre-exercise and at 1, 5 and 10 minutes post-exercise. Before warm-up, the mean blood lactate concentration in male subjects was 1.40 ± 0.24 mmol/L and for female subjects 1.23 ± 0.24 mmol/L. During the first minute of recovery, the post-exercise lactate concentration rose to 9.38 ± 2.18 mmol/L in male sprinters and to 6.73 ± 2.48 mmol/L in female sprinters. Five minutes after the end of the 100 m sprint, the lactate level for females was 11.01 ± 2.14 mmol/L and for males 10.11 ± 0.99 mmol/L. Lactate concentrations at 10 minutes post-exercise reached 9.51 ± 1.23 mmol/L for male sprinters and 9.09 ± 1.46 mmol/L for female sprinters. The observed blood lactate concentration changes in Polish elite sprinters after a 100 m race provide new information regarding recovery dynamics which can be useful in designing sprint training.